Controlling Size‐Induced Phase Transformations Using Chemically Designed Nanolaminates1. Issue 50 (16th October 2013) - Beekman, Matt; Disch, Sabrina; Rouvimov, Sergei; Kasinathan, Deepa; Koepernik, Klaus; Rosner, Helge; Zschack, Paul; Neumann, Wolfgang S.; Johnson, David C.
<x xml:space="preserve">Abstract</x> By dimensionally constraining crystalline layers in a non‐epitaxial intergrowth, nanocrystal ensembles with well‐defined and precisely controlled size are prepared. Synchrotron X‐ray diffraction, electron microscopy, and density functional theory show that a size‐induced second‐order structural transition allows the crystal structure of a layered semiconductor (SnSe) to be continuously tuned by controlling the thickness of the individual layers.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>